2017
DOI: 10.1016/j.aogh.2017.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Student Reflection Papers on a Global Clinical Experience: A Qualitative Study

Abstract: This study provided a method for understanding the student's experience that included student's learning about culture, health disparities, and exposure and reaction to a range of diseases actually encountered. The broad diversity of themes among students indicated that the GCE provided a flexible, personalized experience. How we might design a curriculum to facilitate transformational learning experiences needs further research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…Finally, it should be noted that only one included study indicated that the work conducted had provided no evidence of TL and described the experience of students struggling with the uncertainty and challenges that they are presented with, specifically with regards to ethical issues . These authors and others call for curriculum renewal to prepare students in advance for such learning initiatives.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, it should be noted that only one included study indicated that the work conducted had provided no evidence of TL and described the experience of students struggling with the uncertainty and challenges that they are presented with, specifically with regards to ethical issues . These authors and others call for curriculum renewal to prepare students in advance for such learning initiatives.…”
Section: Resultsmentioning
confidence: 99%
“…27,28 Attempts have been made to develop measures such as surveys, structured instruments, and self-assessments in order to objectively assess global health competencies, but more research is needed in this area, including developing validated measures to assess global health capstones. 12,29,30…”
Section: Limitationsmentioning
confidence: 99%
“…As a result, trainees develop a more nuanced understanding of healthcare delivery across settings, which may also sharpen their ability to perceive such differences locally. By challenging trainees’ cognitive schema and providing opportunities to experience vulnerability in controlled settings, GHE programs do not just teach trainees about health worldwide, but have the potential to profoundly impact their values, clinical practice, and interactions within their local healthcare systems [16]. …”
Section: What Is the Value Of Ghe In An Era Of Rising Anti-global Senmentioning
confidence: 99%
“…They are also core principles of GHE. GHE programs foster relationships with international partners, drive advocacy, and mentor trainees to be effective change agents [58916171920]. Trainees observe role models working alongside local and national leaders on an array of issues including program implementation, health determinants, social justice, human rights, and access to equitable care.…”
Section: What Is the Value Of Ghe In An Era Of Rising Anti-global Senmentioning
confidence: 99%
See 1 more Smart Citation